DILEMATIKA TUMPANG TINDIH DEFINISI DALAM QANUN NO. 6 TAHUN 2014 TENTANG QANUN JINAYAT - Dahlan, Teuku (LEGALITE, 2016)
The Aceh government has conducted contemporary ijtihad in defining khalwat and ikhtilath. There is a khalwat and ikhtilath in the hadith of the Prophet, but the meaning of both is limited to two acts that should be shunned and avoided. Ijtihad conducted by the Aceh government seems to want to realize the meaning of khalwat and ikhtilath that can prevent the people of Aceh to commit adultery. Because khalwat and ikhtilath both are ta'zir, both prazine actions that allow for adultery, Both done by two people of different sexes. Both done by two people who do not have mahram bonds, both can occur in open, closed and hidden places. (But khalwat in open places can not be punished). Then the researchers unite the mention of the finger into the experiment of intercourse and redefined as "The act of being in the open or closed between two or more people of different sex not mahram and without marital bond that leads to Adultery without coercion from another party.